Comparing Coping Strategies Practiced and its association with stress among medical Students from a Private and Public Medical University - Myat Moe Thwe, Aung; Vidya, Bhagat; Tneswari, Masilamani (2018)
Introduction: Medical education has been considered highly stressful to medical students. It not only affects medical students’ physical and mental health but chronic stress can impair academic performance, personal and professional development, leading to unsatisfactory patient care. The objective of this study is to compare the coping strategies practiced and its association with stress between medical students from a private and public university. Materials and Methods: This was a cross-sectional study conducted in a public and private university namely, University Sultan Zainal Abidin (UniZSA) and UCSI University (UCSI) respectively. A total of 245 medical students from UniZSA and 315 medical students from UCSI, from year 1 to year 5 participated in this study. This study was carried out between 2015 till 2016. A universal sampling method was used. A selfadministered questionnaires comprising of 3 sections namely sociodemographic information, 12 item validated General Health Questionnaire (GHQ-12) and a 28 item validated Brief Cope Inventory was used in this study. Data entry and analysis were done using SPSS version 20.0 software. Results: The prevalence of stress was higher (42.2%) among UCSI University medical students compared to University Sultan Zainal Abidin medical students (33.1%). The commonly practised coping strategies in both universities were religion, active coping, acceptance, planning, and positive reframing. The negative coping strategies behavioural disengagement and substance abuse were the least practised in both universities. The associated coping strategies with stress were denial (χ 2 5.740; P<0.05 for UniZSA and χ 2 13.31; P<0.001 for UCSI), behavioural disengagement; (χ2 19.306; P<0.001 for UniZSA and χ 2 7.65; P<0.05 for UCSI) venting (χ2 28.776; P<0.001 for UniZSA and χ 2 8.56; P<0.05 for UCSI), and self-blame (χ2 10.700; P<0.001 for UniZSA and χ 2 9.94; P<0.05 for UCSI) in both universities, with an additional associated coping strategy; acceptance (χ2 4.277; p<0.05) reported in University Sultan Zainal Abidin. Discussion and conclusion: The stress prevalence was higher among UCSI university students compared to UniZSA medical students. UniZSA medical students practised religion as their highest ranked coping strategy compared to UCSI students who practised active coping. The last 2 ranked coping strategies practised; behavioural disengagement and substance abuse (negative strategies) were similar too. The associated coping strategies with stress were also similar for both universities. Stress management programmes like “Medical Student Well-Being Workshops” should be conducted to further add evidence for the implementation of such interventions for reducing medical student stress.